Religion and pluralism - Azmi Aziz (Penerbit Universiti Kebangsaan Malaysia, 1999)
Nowadays, living in multi-religious societies can be very problematic to some people. As we are living in multi-racial and multi-religious societies, we have to face the problem of every religious as the claimant of truth. Yet, if every religion is true, then none of them is true actually. And this is impossible. To solve this problem, many philosophers have offer their outstanding theories. One of them is John Hick who puts forward the idea of pluralism. Yet, can pluralism solve the issue of every religion as a claimant of truth? This article will critically evaluate Hick’s idea of pluralism as well as exclusivism and inclusivism ideas